The Kelp Macrocystis Pyrifera as Nutritional Supplement for Goats - Mora Castro, Nidia; Casas Valdez, Margarita; Marín ílvarezAlejandro; íguila RamírezRuth Noemí; Sánchez Rodríguez, Ignacio; Hernández Contreras, Hugo; Sanginés García, Leonor (Revista Científica de la Facultad de Ciencias Veterinarias)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; p mso-margin-top-alt:auto; margin-right:0cm; mso-margin-bottom-alt:auto; margin-left:0cm; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–>The present study was aimed to evaluate Macrocystis pyrifera (MP) meal as a nutritional supplement for goats. There is an increasing interest to look at nutritional alternatives to guarantee a continuous supply of good quality forage for goats, in many communities around the world. Given its abundance and chemical composition, the algae M. pyrifera is an important potential resource as animal feed. Three diets with 10, 20, and 30% of MP meal concentrations and a control diet, with no algae, were evaluated. Four rumen cannulated goats, housed individually in metabolism cages, were used. The experimental design was a 4 x 4 Latin-Square. Feed and water intake, excreted urine and faeces, were measured. Digestibility in vivo, dry matter (DM) disappearance, and the metabolic variables of pH and ammoniacal nitrogen in the rumen, were determined. There was no significant difference in the feed intake but there was in water intake and urine excreted. No significant difference in digestibility in vivo among diets (P>0.05) was found. A significant difference (P<0.05) for degradability in situ was found for the algae diets containing 10 and 30% MP concentrations at 96 hours of sampling (78.3 and 82.2%). The raw algae in situ digestibility was 77%. A potential degradability of 87.3% was obtained with 30% MP diet. The highest effective degradation was obtained at an estimated rate of 0.02 h-1. Ruminal pH was higher (P<0.05) in all MP treatments (10% MP: 6.83, 20% MP: 6.85, 30% MP: 6.91). As suggested by the results, M. pyrifera represents a good unconventional feeding as a nutritional supplement for goats